2020
DOI: 10.1007/s13204-020-01454-3
|View full text |Cite
|
Sign up to set email alerts
|

High performance of talented copper/magneso-zinc titanate nanostructures as biocidal agents for inactivation of pathogens during wastewater disinfection

Abstract: In the present research, the performance of MZT nano-titanate was established by combining (0.3-0.5) copper nanoparticles (0-0.5C-MZT) to improve the antimicrobial efficacy of promising engineered nanomaterials. XRD characterized the phase purity confirms the formation of magneto-zinc and copper titanates at 750 °C. The morphological features of four engineering nanoceramics were accurately described. As well, the inactivation effects of microbial growth were also evaluated for these kinds of engineered nanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…The EC 50 % level of 500 mg/L of Ag + ions was 73 (moderate toxic effect). This means that the safe tested substances were not affected the luminescent marine bacteria in which utilized as a toxicity bioindicator (Malah et al., 2020; Nahrawy, Bakr, Hammad, & Hemdan, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The EC 50 % level of 500 mg/L of Ag + ions was 73 (moderate toxic effect). This means that the safe tested substances were not affected the luminescent marine bacteria in which utilized as a toxicity bioindicator (Malah et al., 2020; Nahrawy, Bakr, Hammad, & Hemdan, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Ahmad et al reported on PANI nanoparticles that enhanced water permeability and improved the anti-fouling performance of membranes, which was due to an increase in hydrophilicity. Moreover, in the literature, researchers demonstrated that PANI–H 2 O complexes formed as a result of H–O----H–N and C–N----H–O intermolecular hydrogen bond formation [ 38 , 39 , 40 ]. This strengthened the interaction between PANI and water molecules, which resulted in high water permeation.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, no reports on the antibacterial activities of PANI-coated PPSU membranes against E. coli and S. aureus have been published. E. coli and S. aureus were used in this study, because these strains are generally used as biological indicators to assess water contamination [ 40 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few decades, nanoparticles have been used for human welfare in different fields (Sharma et al, 2019). In recent time an intense scientific exploration is ongoing on nanoparticles due to its potential applications in various fields including medical science (Singh and Nalwa, 2011), drug delivery (Medhi et al, 2020), electronics (Magdassi et al, 2010;Kim et al, 2010), optics (Li et al, 2010;Biju et al, 2008), agriculture (Ghasemnezhad et al, 2019;Scott and Chen, 2013), waste water treatment (El Nahrawy et al, 2019;Nahrawy et al, 2020), as sensor support (Abou-Hammad et al, 2019) among others (Guang et al, 2021;Han et al, 2021;Shen et al, 2021;Zhou et al, 2021). The prospective applications of NPs in various fields are premised on the nanoparticle's unique characteristics such as its shape, charge, size, high ratio of surface area to mass and, high reactivity.…”
Section: Introductionmentioning
confidence: 99%